Evaluation of Steel Shear Walls Behavior with Sinusoidal and Trapezoidal Corrugated Plates - Emad Hosseinpour; Shahrizan Baharom; Yasser Yadollahi (Advances in Civil Engineering)
Reinforcement of structures aims to control the input energy of unnatural and natural forces. In the past four decades, steel shear walls are utilized in huge constructions in some seismic countries such as Japan, United States, and Canada to lessen the risk of destructive forces. The steel shear walls are divided into two types: unstiffened and stiffened. In the former, a series of plates (sinusoidal and trapezoidal corrugated) with light thickness are used that have the postbuckling field property under overall buckling. In the latter, steel profile belt series are employed as stiffeners with different arrangement: horizontal, vertical, or diagonal in one side or both sides of wall. In the unstiffened walls, increasing the thickness causes an increase in the wall capacity under large forces in tall structures. In the stiffened walls, joining the stiffeners to the wall is costly and time consuming. The ANSYS software was used to analyze the different models of unstiffened one-story steel walls with sinusoidal and trapezoidal corrugated plates under lateral load. The obtained results demonstrated that, in the walls with the same dimensions, the trapezoidal corrugated plates showed higher ductility and ultimate bearing compared to the sinusoidal corrugated plates.